KORELASI RIBA,ZAKAT DAN SHODAQOH DALAM TEORI BATAS MUHAMMAD SYAHRUR - Ahmad Hamdani (IAIN Kudus, 2017)
Thisarticlewants to expose the thinking of a controversial Syrian thinker,Prof.Ir. Muhammad Syahrur about the correlation of usury, zakah and shodaqoh. The correlation between these three things to explain one of the forms of boundary theory he found. According to Syahrur usury and zakat contained in the theory of the sixth limit is